Imposition of Automation Taxes: a Control Approach for the Replacement of Human Labour - Nivakan, Sritharan; Salawati, Sahari; Cheuk, Sharon Choy Sheung; Mohamed Ahmad, Syubaili (Malaysian Business, 2023)
Having a strong theoretical base, the areas of automation and employment remain critical. The World Economic Forum highlighted that with the help of automation and artificial intelligence, the fourth industrial revolution would result in a major disruption to the labour market. It may affect the workforce in terms of gender, forming a massive gender gap in the future. This article is produced aiming at (1) controlling the implementation of technology and (2) imposing automation taxes through the existing tax policy on capital allowance management. Depreciation on fixed assets, such as the types of machinery and tools, are generally non-deductible expenses under tax computation in many countries.